PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III UPT SD INPRES BORONG - Ramadhani, Tri; A Husniati; Hadaming, Hamdana (Universitas Muhammadiyah Makassar, 2025)
This research is motivated by the problem of learning outcomes that occur in UPT SD Inpres Borong, especially for third-grade students. The problems that occur are influenced by several factors, both from student factors, learning motivation, or inadequate learning environment. Therefore, researchers provide an alternative solution to the problem, namely by using the Contextual Teaching and Learning approach in the learning process so that learning becomes more enjoyable and effective. The purpose of this study is to determine the effect of the Contextual Teaching and Learning approach on the mathematics learning outcomes of third-grade students of UPT SD Inpres Borong. The research approach used is a quantitative approach with a Pre-experimental research type. The research design is One Group Pretest-Posttest Design. The subjects used in this study were 31 third-grade students. The research instruments used were learning outcome tests and observation sheets. The data analysis techniques used were descriptive data analysis and inferential data analysis. The results of the inferential statistical analysis using the t-test, it is known that the t-count value = 12.47 while the t-table value = 1.697 at a significance level of α = 0.05. Based on these values, it is obtained that t-count > t-table, this means that H0 is rejected and then H1 is accepted. The results of the analysis of student observation sheets in the class accumulated from the first to the third meeting obtained a score of 431.2 with a percentage of 72% which indicates student involvement in the good category. Based on these results, it can be concluded that there is a significant influence by using the Contextual Teaching and Learning approach on the mathematics learning outcomes of class III students of UPT SD Inpres Borong.